A retrospective analysis of outcomes of rhino-orbito-cerebral mucormycosis at tertiary care hospital - Bellary, Radhika; Channashetti, Gajanan; K., Sharath Babu; S. R., Lavanya; Dhage, Vaishnavi Suresh (International Journal of Research in Medical Sciences, 2025)
Background: This study aimed to report outcomes of rhino-orbital-cerebral mucormycosis (ROCM) at tertiary care centre. Methods: Retrospective analysis of in-patients diagnosed to have ROCM during the year 2021 was done. Diagnosis was confirmed based on lab and MRI investigations. Clinical features and management outcomes were noted. Results: Among 113 suspected cases, 81 were confirmed to have ROCM. Majority of the patients had suffered COVID-19 disease. 67 cases out of 81 underwent maxillectomy with sinus debridement. Among the 67 cases,11 patients had orbital involvement with no PL, orbital exenteration was performed. Among remaining 14 patients, mortality due to cardiac and respiratory illness was seen in 3 patients, 7 went against advice and 4 had CNS involvement. All the patients were treated with liposomal amphotericin-B. Conclusions: Early diagnosis, surgical intervention followed by amphotericin B in ROCM has favourable outcome. CNS involvement has a high mortality rate.